Preparation of high temperature sensible heat storage materials from reduced vanadium tailings and graphite - Rongxun Piao; Xuan Li; Peng Zhao (Materials Research Express, 2021)
The experimental study on the preparation of high temperature (>500 °C) sensible heat storage materials (SHS) was conducted through the means of sintering method, in which vanadium tailings after carbothermic reduction used as the main matrix, graphite as the thermal conductivity modifier, and clay as the auxiliary material. The phase analysis by XRD shows that the main phases of the SHS materials without clay addition are aluminosilicate, sodium aluminoslicate, ilmenite and graphite, while additional phases of quartz and carbonate were observed if clay is added. With the graphite addition ranging from 0 to 15%, the density and hardness of the SHS materials without clay addition generally shows decreasing tendency while both properties behave increasing first and then decreasing in the SHS materials with clay addition. In addition, with increase of graphite, thermal conductivity of material without adding clay gradually increases in a range of 0.54 ∼ 1.54 W·m ^−1 ·K ^−1 , while thermal conductivity of materials with adding clay remains unchanged first and then increases in the range of 0.754 ∼ 1.922 W·m ^−1 ·K ^−1 .Thermal analysis shows that when the graphite content is 3 ∼ 5%, both SHS materials without or with clay have moderate specific heat capacity and high thermal capacity (>1.2 MJ m ^−3 ·K) at temperate above 500 °C, and high heat storage density (>200 kJ kg ^−1 ) in the temperature range of 500 °C ∼ 750 °C, indicating SHS materials prepared in this study can be considered for application in high temperature storage system.